2012
DOI: 10.1111/j.1365-2966.2012.21329.x
|View full text |Cite
|
Sign up to set email alerts
|

P/2006 VW139: a main-belt comet born in an asteroid collision?

Abstract: In this paper, we apply different methods to examine the possibility that a small group of 24 asteroids dynamically linked to a main‐belt comet P/2006 VW139, recently discovered by the Pan‐STARRS1 survey telescope, shares a common physical origin. By applying the hierarchical clustering and backward integration methods, we find strong evidence that 11 of these asteroids form a sub‐group which likely originated in a recent collision event, and that this group includes P/2006 VW139. The objects not found to be p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 69 publications
0
48
0
Order By: Relevance
“…The layering of composition, or internal heterogeneity, could in this case explain the spectral variability observed among Themis family members, which cannot be completely explained by space weathering processes . Among the Themis family lie much younger sub-families: the Beagle family, aged less than 10 Myr (Nesvorný et al 2008), and the 288P cluster, estimated to be 7.5 Myr old (Novaković et al 2012). It is possible that MBCs 133P and 288P may be members of those young sub-families rather than primordial members of the Themis family, increasing the possibility that water ice-if initially present in the various precursors-could have survived in both objects until today.…”
Section: Family Originsmentioning
confidence: 99%
“…The layering of composition, or internal heterogeneity, could in this case explain the spectral variability observed among Themis family members, which cannot be completely explained by space weathering processes . Among the Themis family lie much younger sub-families: the Beagle family, aged less than 10 Myr (Nesvorný et al 2008), and the 288P cluster, estimated to be 7.5 Myr old (Novaković et al 2012). It is possible that MBCs 133P and 288P may be members of those young sub-families rather than primordial members of the Themis family, increasing the possibility that water ice-if initially present in the various precursors-could have survived in both objects until today.…”
Section: Family Originsmentioning
confidence: 99%
“…Several main-belt comets (MBC) (Hsieh & Jewitt 2006) have been dynamically linked to the Themis family (Hsieh 2009;Novaković et al 2012). The source of sublimation in these MBCs is attributed to water ice buried beneath a layer of regolith several meters thick (Schorghofer 2008;Prialnik & Rosenberg 2009).…”
Section: Aqueous Alteration In the Themis Parent Bodymentioning
confidence: 99%
“…Meanwhile, thermal modeling studies have shown that despite the fact that surface ice on main-belt objects today is highly unstable against sublimation, subsurface ice could potentially remain preserved over the age of the solar system (Schorghofer 2008;Prialnik & Rosenberg 2009). The same impact excavation events thought to trigger current MBC activity (Hsieh et al 2004) will still deplete the volatile content of an asteroid's upper surface layers over Gyr timescales (Hsieh 2009), but the membership of at least two MBCs in extremely young asteroid families (Nesvorný et al 2008;Novaković et al 2012) suggest that recent catastrophic disruptions of larger ice-bearing bodies could result in a significant population of objects with subsurface ice at depths shallow enough to be susceptible to impact excavation and therefore triggering of sublimation-driven activity.…”
Section: Are They Actually Icy?mentioning
confidence: 99%
“…These objects have not simply undergone dynamical evolution though, of course, and as such, other processes that have acted on MBCs over time, such as thermal depletion of volatiles, collisional depletion, and catastrophic disruptions (cf. Schorghofer 2008;Hsieh 2009;Nesvorný et al 2008;Novaković et al 2012), will also need to be studied and well-understood in order for useful information to be inferred about the primordial protosolar disk from the MBCs.…”
Section: Looking Aheadmentioning
confidence: 99%